Effect of high pressure on the proteolytic activity and autolysis of yeast Saccharomyces cerevisiae. (December 2021) - Dimopoulos, George; Limnaios, Athanasios; Aerakis, Evangelos; Andreou, Varvara; Taoukis, Petros
Abstract: This work explores the effect of High Pressure (HP) treatment on the proteolytic activity and autolytic capacity of Saccharomyces cerevisiae suspensions, based on yeast extract production. Cellular suspensions were treated at 200–600 MPa for 0–120 min and the activity of vacuolar proteases was measured during autolysis. Moreover, the autolytic capacity of yeast was determined based on the physicochemical characteristics of the produced yeast extract. At pressures of 200 and 400 MPa, proteolytic activity was enhanced up to 160%, after 40 and 10 min of HP treatment, respectively, leading to significantly accelerated autolysis, in combination with cellular permeabilization achieved with HP treatment. However, at 600 MPa, despite the greater cell permeabilization, proteolytic enzymes were gradually inactivated (total inactivation after 15 min of HP treatment), leading to inhibition of autolysis. These results highlight HP as an effective process to enhance endogenous proteolytic activity and thus accelerate yeast extract production. Highlights: HP treatment affects both cell permeability and proteolytic activity of yeast cells HP can increase the activity of vacuolar proteases during autolysis Treatment pressures up to 400 MPa significantly enhance autolysis Treatment pressures over 600 MPa inhibit autolysis